Surface Layer States of Worn Uncoated and TiN-Coated WC/Co-Cemented Carbide Cutting Tools after Dry Plain Turning of Carbon Steel. (24th February 2013) - Kümmel, Johannes; Poser, Katja; Zanger, Frederik; Michna, Jürgen; Schulze, Volker
Abstract : Analyzing wear mechanisms and developments of surface layers in WC/Co-cemented carbide cutting inserts is of great importance for metal-cutting manufacturing. By knowing relevant processes within the surface layers of cutting tools during machining the choice of machining parameters can be influenced to get less wear and high tool life of the cutting tool. Tool wear obviously influences tool life and surface integrity of the workpiece (residual stresses, surface quality, work hardening, etc.), so the choice of optimised process parameters is of great relevance. Vapour-deposited coatings on WC/Co-cemented carbide cutting inserts are known to improve machining performance and tool life, but the mechanisms behind these improvements are not fully understood. The interaction between commercial TiN-coated and uncoated WC/Co-cemented carbide cutting inserts and a normalised SAE 1045 steel workpiece was investigated during a dry plain turning operation with constant material removal under varied machining parameters. Tool wear was assessed by light-optical microscopy, scanning electron microscopy (SEM), and EDX analysis. The state of surface layer was investigated by metallographic sectioning. Microstructural changes and material transfer due to tribological processes in the cutting zone were examined by SEM and EDX analyses.